The role of between- and within-occupation differences in wage inequality trends in Europe (2002-2018) - Guillermo Orfao e Vale Tabernero; Enrique Fernández-Macías; Miguel Angel Malo Oca\~na (European Commission, Joint Research Centre (JRC), 2024)
This working paper presents a comparative analysis of the role played by occupational changes in recent wage inequality trends in six European countries between 2002 and 2018. Using the European Union Structure of Earnings Survey, the analysis shows two patterns in the share of wage inequality explained by between-occupation differentials: while the relative importance of between-occupation trends has grown in Finland and the UK, it has diminished in Spain, France, Poland and Romania. Although between-occupation differentials account for a great share of total wages' variance, changes in the occupational structure (in particular, the patterns of job polarisation and upgrading widely discussed in the literature) have not driven recent wage inequality trends in Europe. Wage inequality, instead, has been mostly driven by changes in wage differentials within occupations. Finally, we found that occupations effectively account for the distribution of wages, yet their explanatory significance markedly declines at the highest wage tiers. This work contributes to a better understanding of how within- and between-occupation differences have influenced wage inequality trends in Europe. Consequently, our results add significant value to the debate about recent stratification theory, which has challenged the idea that occupations structure economic disparities and wage inequality as importantly as they once did.
Keywords: 330; Europe; jobs; occupational structure; occupations; wage inequality